Injectable, Hyaluronic Acid-Based Scaffolds with Macroporous Architecture for Gene Delivery - Ehsanipour, Arshia (Cell Mol Bioeng, 2019)
INTRODUCTION: Biomaterials can provide localized reservoirs for controlled release of therapeutic biomolecules and drugs for applications in tissue engineering and regenerative medicine. As carriers of gene-based therapies, biomaterial scaffolds can improve efficiency and delivery-site localization of transgene expression. Controlled delivery of gene therapy vectors from scaffolds requires cell-scale macropores to facilitate rapid host cell infiltration. Recently, advanced methods have been developed to form injectable scaffolds containing cell-scale macropores. However, relative efficacy of in vivo gene delivery from scaffolds formulated using these general approaches has not been previously investigated. Using two of these methods, we fabricated scaffolds based on hyaluronic acid (HA) and compared how their unique, macroporous architectures affected their respective abilities to deliver transgenes via lentiviral vectors in vivo. METHODS: Three types of scaffolds—nanoporous HA hydrogels (NP-HA), annealed HA microparticles (HA-MP) and nanoporous HA hydrogels containing protease-degradable poly(ethylene glycol) (PEG) microparticles as sacrificial porogens (PEG-MP)—were loaded with lentiviral particles encoding reporter transgenes and injected into mouse mammary fat. Scaffolds were evaluated for their ability to induce rapid infiltration of host cells and subsequent transgene expression. RESULTS: Cell densities in scaffolds, distances into which cells penetrated scaffolds, and transgene expression levels significantly increased with delivery from HA-MP, compared to NP-HA and PEG-MP, scaffolds. Nearly 8-fold greater cell densities and up to 16-fold greater transgene expression levels were found in HA-MP, over NP-HA, scaffolds. Cell profiling revealed that within HA-MP scaffolds, macrophages (F4/80+), fibroblasts (ERTR7+) and endothelial cells (CD31+) were each present and expressed delivered transgene. CONCLUSIONS: Results demonstrate that injectable scaffolds containing cell-scale macropores in an open, interconnected architecture support rapid host cell infiltration to improve efficiency of biomaterial-mediated gene delivery. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12195-019-00593-0) contains supplementary material, which is available to authorized users.